2015
DOI: 10.1111/vec.12343
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of methionine intoxication associated with urinary acidifying products in dogs: 1,525 cases (2001–2012)

Abstract: Prognosis for dogs with methionine intoxication is excellent. Vomiting and ataxia were the most common clinical signs associated with methionine toxicosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A couple of studies evaluating the effect of calcium sulphate supplementation in dogs (3.17 g S/kg of diet, Janczikowski et al, 2008) and cats (2.56 g S/kg of diet, Halfen et al, 2018) showed only a small and not significant urinary pH acidification effect, this result might have been due to a low intake of calcium sulphate, which was probably insufficient to produce significant urinary acidification. Multiple studies verified the effectiveness of L-methionine/DL-methionine as a urinary acidifier in humans, cats and dogs (Funaba et al, 2001;Halfen et al, 2018;Hickey et al, 2015;Jacobs et al, 2001;Siener et al, 2016;).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A couple of studies evaluating the effect of calcium sulphate supplementation in dogs (3.17 g S/kg of diet, Janczikowski et al, 2008) and cats (2.56 g S/kg of diet, Halfen et al, 2018) showed only a small and not significant urinary pH acidification effect, this result might have been due to a low intake of calcium sulphate, which was probably insufficient to produce significant urinary acidification. Multiple studies verified the effectiveness of L-methionine/DL-methionine as a urinary acidifier in humans, cats and dogs (Funaba et al, 2001;Halfen et al, 2018;Hickey et al, 2015;Jacobs et al, 2001;Siener et al, 2016;).…”
Section: Discussionmentioning
confidence: 92%
“…A couple of studies evaluating the effect of calcium sulphate supplementation in dogs (3.17 g S/kg of diet, Janczikowski et al., 2008) and cats (2.56 g S/kg of diet, Halfen et al., 2018) showed only a small and not significant urinary pH acidification effect, this result might have been due to a low intake of calcium sulphate, which was probably insufficient to produce significant urinary acidification. Multiple studies verified the effectiveness of l ‐methionine/ dl ‐methionine as a urinary acidifier in humans, cats and dogs (Funaba et al., 2001; Halfen et al., 2018; Hickey et al., 2015; Jacobs et al., 2001; Siener et al., 2016;). In the present study, urinary pH oscillated between 5.30 and 6.16 when the dogs were fed the Urinary S/O diet, and although the present study was not designed to determine the impact of any specific nutrient on urinary pH, it is expected that the methionine content of this diet had a major influence on its acidifying effect.…”
Section: Discussionmentioning
confidence: 94%
“…In order to formulate the right questions, design and carry out prospective studies, we do rely on having ample descriptive data about the clinical presentation, the course of progression, and outcome of animals affected by various toxins. So contributions such as those made by Hickey et al, DuHadway et al, and Katzenbach et al each provide needed data to improve our understanding of the toxicities presented and the clinical course of intoxications. It is with these types of information that we can one day evaluate efficacy of novel treatment protocols.…”
mentioning
confidence: 99%